The woods. Vol. 1, The arrow - Tynion, James, IV (Boom! Studios, 2014)
On October 16, 2013, 437 students, 52 teachers, and 24 additional staff from Bay Point Preparatory High School in suburban Milwaukee, WI vanished without a trace. Countless light years away, far outside the bounds of the charted universe, 513 people find themselves in the middle of an ancient, primordial wilderness. Where are they? Why are they there? The answers will prove stranger than anyone could possibly imagine.